Effect of aspirin in vascular surgery in patients from a randomized clinical trial (POISE-2). Issue 12 (18th July 2018) - Biccard, B M; Sigamani, A; Chan, M T V; Sessler, D I; Kurz, A; Tittley, J G; Rapanos, T; Harlock, J; Szalay, D; Tiboni, M E; Popova, E; Vásquez, S M; et al.
Abstract: Background: In the POISE-2 (PeriOperative ISchemic Evaluation 2) trial, perioperative aspirin did not reduce cardiovascular events, but increased major bleeding. There remains uncertainty regarding the effect of perioperative aspirin in patients undergoing vascular surgery. The aim of this substudy was to determine whether there is a subgroup effect of initiating or continuing aspirin in patients undergoing vascular surgery. Methods: POISE-2 was a blinded, randomized trial of patients having non-cardiac surgery. Patients were assigned to perioperative aspirin or placebo. The primary outcome was a composite of death or myocardial infarction at 30 days. Secondary outcomes included: vascular occlusive complications (a composite of amputation and peripheral arterial thrombosis) and major or life-threatening bleeding. Results: Of 10 010 patients in POISE-2, 603 underwent vascular surgery, 319 in the continuation and 284 in the initiation stratum. Some 272 patients had vascular surgery for occlusive disease and 265 had aneurysm surgery. The primary outcome occurred in 13·7 per cent of patients having aneurysm repair allocated to aspirin and 9·0 per cent who had placebo (hazard ratio (HR) 1·48, 95 per cent c.i. 0·71 to 3·09). Among patients who had surgery for occlusive vascular disease, 15·8 per cent allocated to aspirin and 13·6 per cent on placebo had the primary outcome (HR 1·16, 0·62 to 2·17). There was no interaction with the primary outcome for type of surgery ( P = 0·294) or aspirin stratum ( P = 0·623). There was no interaction for vascular occlusive complications ( P = 0·413) or bleeding ( P = 0·900) for vascular compared with non-vascular surgery. Conclusion: This study suggests that the overall POISE-2 results apply to vascular surgery. Perioperative withdrawal of chronic aspirin therapy did not increase cardiovascular or vascular occlusive complications. Registration number: NCT01082874 (http://www.clinicaltrials.gov ). Abstract : No evidence to start or stop aspirin